Ekonomi Politik Media dalam Kreasi Video Let’s Play di Indonesia (Kasus YouTuber ‘MiawAug’) - Dahana, Abyzan Syahadin Bagja; Yuwono, Ardian Indro (Jurnal Media dan Komunikasi, 2025)
This study aims to uncover the practice of media political economy among Let’s Play (LP) video creators in Indonesia, with a focus on the YouTuber MiawAug. LP content is gaining popularity among gamers; however, prior research has generally only highlighted commodification aspects related to creators and audiences. Using Vincent Mosco's theory of media political economy, this study analyzes MiawAug's practices of commodification, spatialization, and structuration in content creation. The researchers employed descriptive qualitative methods, collecting data from literature reviews and document analysis related to the MiawAug YouTube channel. Findings reveal that MiawAug engages in commodification processes—specifically content, audience, and labor commodification—by producing videos featuring popular games to generate ad revenue. Additionally, MiawAug implements spatialization through the use of diverse media platforms, collaboration with other creators, and merchandise sales. MiawAug also employs structuration by using polite language in videos, setting himself apart from many gaming content creators who use swearing as an entertainment element. Furthermore, he leverages his popularity to promote indie games, encouraging viewer support through video promotions.